ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU RBDPS PADA PROSES FATTY ACID DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DI PT. X - Romatua Pasaribu; Masdania Zurairah Siregar; Rahmad Rezeki (Sekolah Tinggi Pariwisata Mataram, 2022)
In this research, how to control the supply of RBDPS raw materials in the fatty acid process used the economical order Quantity (EOQ) method at PT X. The stages for producing fatty acid splitting, the glycerine pre-treatment stage, the glycerine evaporation stage, the glycerine distillation stage, the hydrogenation stage and fatty acid distillation stages. The EOQ method provides benefits to companies with savings in inventory costs. A significant influence lies in storage costs, there is a very drastic change from Rp. 127,545,434.03 to Rp. 64,419,560.90 with a difference of Rp. 63,125,873.13. From the total inventory cost, it can also be seen that the company's inventory cost is Rp. 163,856,234.03, while using the EOQ method the inventory cost is Rp. 128,839,077.79 resulting in a savings of Rp. 35,019,165.24.